Phytosociological Studies on the Vegetation or Sand Dunes of Sikar, Rajasthan - Sharma, B. M. (Indian Forester, 1972)
The present paper deals with the phytosocilogical studies on the vegetation of sand dunes around Sikar, RaJasthan. Five plant communities have been recognized in the various localities during the rainy season. The phytosocilogical characters with reference to the frequency, density, abundance and periodicity have been given.